Perlindungan Hukum Atas Pemutusan Hubungan Kerja Pada PT Hollit International (Analisis Putusan Mahkamah Agung Nomor 971 K/Pdt. Sus-PHI/2018) - Iis Apriyani; Indra Rahmatullah (JOURNAL of LEGAL RESEARCH, 2020)
The problem that will be examined in this research with the object of the ruling is variatively related to the fulfillment of labor rights in the LAYOFFS thus causing the uncertainty of law on the procedure and fulfillment of rights-normative rights in fulfilling the rights of the diPHK workers. Like one case PT. Hollit International, which in the first-level decision of the Tribunal judges rejected the suit of all rights of workers, but at the rate of appeal, the Tribunal cancelled the court of first degree, as the Industrial Relations Tribunal at the Central Jakarta District Court had misapplied the law. This research uses a qualitative research type that is the type of data and the analysis used is narrative, in the form of statements that use reasoning. Using a normative juridical approach, referring to the application of the law contained in a verdict and the law conceptualized as the norm or the rules applicable in society. The results show the demands of the rights of workers in LAYOFFS by the company, with the ruling that is not comprehensive and less synchronous between the manpower law and the ruling in the Industrial relations Court at the Central Jakarta District Court, causing uncertainties in the process of fulfilling the rights of workers. Kata kunci : Hak, Tenaga Kerja, Mutasi, Pemutusan Hubungan Kerja.